ChemChina - McFarlan, F. Warren (Franklin Warren); Li, Donghong; Li, Lei; Zhang, Hong (Economist) ([London] : SAGE, 2016)
By 2011, seven years after incorporation, ChemChina's total assets had increased by 10.8 times, revenues by 11.3 times, total profit by 10.7 times, due to organic growth and a series of M&As. Today, ChemChina is China's largest chemical manufacturing firm. It is No.9 among the world's Chemical 100, and No.402 in the Fortune 500 in 2012. Recalling the last 27 years since BlueStar, now one of the two pillar subsidiaries of ChemChina, grew up from nothing, President Ren Jianxin notes ChemChina is not yet a powerful corporation. Although a strategic path has been worked out, much work is needed to make it globally competitive. Today, ChemChina confronts the tasks of internal integration and dealing with financial stringency.
Originally Published in: McFarlan, F. W., Li, D., Li, L. & Zhang, H. (2012). ChemChina. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; ChemChina (Firm); Entrepreneurship -- Case studies; Strategic planning -- Case studies; Business planning -- Case studies